The safety and efficacy of fibrin sealant for thyroidectomy: a systematic review and meta-analysis of randomized controlled trials - Koerniawan, Heru Sutanto; Candrawinata, Valeska Siulinda; Tjahyanto, Teddy; Wijaya, Nicholas Jason; Putra, Aulia Wiratama; Wijaya, Jeremiah Hilkiah (Frontiers in Surgery, 2023)
Fibrin sealants have recently been thoroughly studied in several surgical specialties; however, results are conflicting. We aimed to examine the safety and efficacy of fibrin sealant patients having thyroidectomies. A thorough, systematic literature search was carried out using the terms thyroidectomy and fibrin sealant using PubMed, Cochrane Library, and Clinicaltrials.gov on December 25, 2022. The primary outcome of interest in this review was the amount of drainage, whereas hospitalization, the length of drain retention, and temporary dysphonia were secondary outcomes. Our meta-analysis (n = 249) showed that application of fibrin sealant is associated with lesser total drainage (SMD -2.76 [-4.83, -0.69]; P = 0.009; I2 97%), but not with retention time of drainage (SMD -2.35 [-4.71, 0.01]; P = 0.05; I2 98%), hospitalization time (SMD -1.65 [-3.70, 0.41]; P = 0.12; I2 97%), and transient dysphonia (RR 1.01 [0.27, 3.82]; P = 0.99; I2 0%). The systematic review found that the use of fibrin sealant in thyroid surgery is positive in total volume drainage but not with the retention time of drainage, hospitalization time, and transient dysphonia. It is notable to remember that this interpretation is complicated by uneven, occasionally subpar technique and trial reporting, according to this systematic review's findings.